PROFIL DAN FAKTOR-FAKTOR YANG MEMENGARUHI EFIKASI GURU MADRASAH IBTIDAIYAH PESERTA DUAL MODE SYSTEM - Muna Erawati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
One of critical problem related to Islamic elementary school teacher is disadvantage teacher personality. An important aspect of teacher personality is self-efficacy. This study try to answer three questions — first, how to describe Islamic elementary school efficacy teacher profile? Secondly, what factors contribute to Islamic elementary school teacher efficacy? Thirdly, how to explain the psychological dynamic of Islamic elementary school teacher efficacy? Teacher efficacy was defined as the teacher belief in his or her capability to organize and execute courses of actions to successfully accomplish a specific teaching task in a certain context (Tschannen-Moran, Hoy, Hoy, 1998: 233). There were 132 teachers participating in this survey. They were administered Teacher Efficacy Scale which was developed by Bandura (by permission from Indigenous Psychology Team of Psychology Department of Gadjah Mada University). Teacher efficacy score was about average level to high. Some predictorscontributed significantly toward some teacher efficacy dimensions, but they did not correlate with the total score of teacher efficacy. The implication of this research will discuss later.